Notes on Gerridae (Hemiptera: Heteroptera: Gerromorpha) from the Eastern Ghats of Telangana and Northern Andhra Pradesh, India - DEEPA JAISWAL; SOMESH BANERJEE (Nusantara Bioscience, 2024)
Abstract. Jaiswal D, Banerjee S. 2024. Notes on Gerridae (Hemiptera: Heteroptera: Gerromorpha) from the Eastern Ghats of Telangana and Northern Andhra Pradesh, India. Nusantara Bioscience 16: 43-53. Gerridae is the family of semi-aquatic bugs found in both the lentic and lotic freshwater bodies. The present study focused on the Gerridae from the Eastern Ghats of Telangana and Northern Andhra Pradesh, India. This study documented a total number of 16 species belonging to 13 genera and 7 subfamilies under the family Gerridae. Tenagogonus nicobarensis Andersen, 1964, was earlier described from Andaman and Nicober islands and also known to be endemic to that particular geographical area. We are recording this species for the first time from the mainland of the Indian subcontinent. Ventidius aquarius Distant, 1910 was also recorded for the first time during this present study from the Eastern Ghats, an endemic species to peninsular India. Another species, Naboandelus signatus Distant, 1910 is also recorded from the Eastern Ghats of Andhra Pradesh as well as an addition to the state fauna of Andhra Pradesh. It is a widespread species and reported from both central and northeastern India. In southern India, it was reported from the two states and present record will be the additional third state to its distribution. In addition to taxonomic details, the article covers the geographic distribution of the 16 species. This study has also led to the addition of nine species of Gerridae to the state fauna of Andhra Pradesh.